2019
DOI: 10.1016/j.polymdegradstab.2019.108939
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics as a sensitive tool to detect degradation in poly(lactide)/poly(ε-caprolactone)/ PCL-co-PC copolymers blends

Abstract: Poly(lactide)/poly(-caprolactone) blends (PLA/PCL) with composition 80/20 (w/w%) are immiscible but biodegradable and therefore often studied in the literature. We have prepared 80/20 PLA/PCL blends with and without poly(ε-caprolactone)-co-poly(carbonate) copolymers (block and random). The blends were prepared both by melt extrusion and by solution blending. The concentration of PCL-co-PC copolymers added to the blends was 2 wt%. Compression molded sheets and solvent cast films were evaluated by GPC (Gel Perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The addition of both nucleating and plasticizers agents has also been reported in the literature [10]. Another alternative to improve the crystallization of PLA is blending with other polymers [14,18,19].…”
Section: Introductionmentioning
confidence: 87%
“…The addition of both nucleating and plasticizers agents has also been reported in the literature [10]. Another alternative to improve the crystallization of PLA is blending with other polymers [14,18,19].…”
Section: Introductionmentioning
confidence: 87%
“…Figure 6b shows the overall crystallization rate for PA1012 as a function of T c with different isothermal times at 250 °C. Some studies 50 have demonstrated that the overall crystallization rate first increased as the molecular weight increased, then reached a maximum, and finally decreased. For most commercial polymers, such as polyamides, molecular weights are high enough that they are in the molecular weight range in which the overall crystallization rate decreases with increasing molecular weight.…”
Section: σσmentioning
confidence: 99%
“…Upon biodegradation T d5% for neat PCL decreases from 350 to 323 C, related to the biocomposites decreases even higher were verified all of them presented T d5% lower than neat PCL corroborating with the lower thermal stability of PCL/MF. 59,60 Related to the biodegradation time for longer time the decreasing in the thermal stability was intensified and specimens presented lower T d5% , T d50% , and T dmax after 90 days of biodegradation. Related with the fiber treatment PCL/MF-T presented lower TG parameters than PCL/MF-P.…”
Section: Optical Microscopymentioning
confidence: 99%